1994
DOI: 10.1111/j.1432-1033.1994.tb19938.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll synthetase cannot synthesize chlorophyll a′

Abstract: Chlorophyll synthetase catalyzes the last step of chlorophyll biosynthesis, namely prenylation (esterification) of chlorophyllide with phytyl diphosphate or geranylgeranyl diphosphate. During investigation of various chlorophyllide derivatives as potential substrates we observed lower esterification with increasing percentages of chlorophyllide a' in epimeric mixtures of chlorophyllides a and a: To avoid epimerization during esterification, we studied the reaction in detail with model compounds [zinc-1 32(R)-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 37 publications
4
77
0
Order By: Relevance
“…Preliminary studies of the change of esterification rate with substrate concentration, performed with the method of Helfrich et al (1994), indicated a 'normal' saturation curve for PhyPP ( Figure 3A) and the characteristic of substrate inhibition for Chlide ( Figure 3B) with the optimum reaction rate occurring at 5 -10 µM Chlide. The variation of substrate concentration in the following detailed investigation was therefore limited for Chlide up to about 8 µM, while a range up to 100 µM was used for PhyPP.…”
Section: The Reaction Follows a Ping-pong Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary studies of the change of esterification rate with substrate concentration, performed with the method of Helfrich et al (1994), indicated a 'normal' saturation curve for PhyPP ( Figure 3A) and the characteristic of substrate inhibition for Chlide ( Figure 3B) with the optimum reaction rate occurring at 5 -10 µM Chlide. The variation of substrate concentration in the following detailed investigation was therefore limited for Chlide up to about 8 µM, while a range up to 100 µM was used for PhyPP.…”
Section: The Reaction Follows a Ping-pong Mechanismmentioning
confidence: 99%
“…The reaction was stopped with acetone after specified periods, and the resulting pigment mixture was analyzed for total pigment by spectrophotometry and subsequently by HPLC using a fluorescence detector; this fluorescence assay is more sensitive than that using solvent extraction and absorption measurement as described by Helfrich et al (1994). The sensitivity is especially important for the accurate pigment measurement at the beginning of the reaction, when very little esterified pigment is produced.…”
Section: The Esterification Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation for 45 min at 29 °C, the reaction was stopped by addition of 750 µl acetone, and the precipitated protein was removed through centrifugation. After addition of 40 µl 100 mM Na 2 CO 3 , the clear supernatant was used to quantitate the esterified Chl by phase separation as previously described (Helfrich et al, 1994).…”
Section: Expression Of Chlorophyll Synthase 909mentioning
confidence: 99%
“…The activity of chlorophyll synthase was originally detected in etioplast membranes of Avena sativa L. , and several investigations were performed with this plant material Schoch et al, 1980;Benz and Rüdiger, 1981a, b;Lütz et al, 1981;Helfrich and Rüdiger, 1992;Helfrich et al, 1994). The enzyme showed a higher activity with geranylgeranyldiphosphate acid residues 109 -115 and 358 -366 of the G4 sequence of A. thaliana (Gaubier et al, 1995) were selected for PCR amplification with suitable primers.…”
Section: Introductionmentioning
confidence: 99%